2021
DOI: 10.3390/ijms22158143
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of the Crystal and Cryo-EM Structures of P-Loop Channels with Drugs

Abstract: The superfamily of P-loop channels includes various potassium channels, voltage-gated sodium and calcium channels, transient receptor potential channels, and ionotropic glutamate receptors. Despite huge structural and functional diversity of the channels, their pore-forming domain has a conserved folding. In the past two decades, scores of atomic-scale structures of P-loop channels with medically important drugs in the inner pore have been published. High structural diversity of these complexes complicates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…In our recent studies of bacterial Nav channels NavMs and NavAb, we found that introducing a short π-helical stretch in S6 of the channel resulted in the rotation of the S6 C-terminus and in increased pore hydration, allowing sodium ion permeation. This mechanism is consistent with that described in some TRP channels. , The presence of π-helices in the pore lining helices of different channels with similar architecture is considered to be conserved and to play an important role in drug binding. , Inspired by these observations, we hypothesized that eukaryotic Nav channel opening might involve a transition to the π-helix in one or more of the DI/DII/DIV S6 helices. Additionally, given the heterogeneity of eukaryotic Nav channels and the stabilization of different secondary structures in their S6 helices, we hypothesized that an α-/π-helix conformation in different S6 helices might give rise to different subconductance levels, resulting in different open states.…”
supporting
confidence: 83%
“…In our recent studies of bacterial Nav channels NavMs and NavAb, we found that introducing a short π-helical stretch in S6 of the channel resulted in the rotation of the S6 C-terminus and in increased pore hydration, allowing sodium ion permeation. This mechanism is consistent with that described in some TRP channels. , The presence of π-helices in the pore lining helices of different channels with similar architecture is considered to be conserved and to play an important role in drug binding. , Inspired by these observations, we hypothesized that eukaryotic Nav channel opening might involve a transition to the π-helix in one or more of the DI/DII/DIV S6 helices. Additionally, given the heterogeneity of eukaryotic Nav channels and the stabilization of different secondary structures in their S6 helices, we hypothesized that an α-/π-helix conformation in different S6 helices might give rise to different subconductance levels, resulting in different open states.…”
supporting
confidence: 83%
“…3-D alignment of available structures of P-loop channels suggests that calcium and sodium channels have similar folding of the pore domain, which differs from that in potassium, TRP, and glutamate-gated channels ( Tikhonov and Zhorov, 2021 , 2022 ). Therefore, crystal and cryo-EM structures of sodium and calcium channels can be used as templates to model channel Cav1.1 in different functional states.…”
Section: Resultsmentioning
confidence: 99%
“…Recent structural studies revealed an interesting peculiarity of S6 segments in sodium, calcium, and TRP channels. In some structures, these segments are not entirely α-helical but contain a π-helical turn at a position where the glycine gating hinge is located in potassium channels ( Tikhonov and Zhorov, 2017 , 2021 , 2022 ). Since a π-helix has an extra residue per turn as compared with an α-helix, the π-helical turn is seen as a bulge in the helix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism is consistent with that described in some TRP channels (26,27). The presence of π-helices in the pore lining helices of different channels with similar architecture (28) is considered to be conserved and to play an important role in drug binding (20,29). Inspired by these observations, we hypothesized that eukaryotic Nav channel opening might involve a transition to π-helix in one or more of the DI/DII/DIV S6 helices.…”
mentioning
confidence: 99%